Learning together with young children : a curriculum framework for reflective teachers - Curtis, Deb; Carter, Margie, 1942- (St. Paul, MN : Redleaf Press, 2017)
'Each chapter in this curriculum framework includes a conceptual overview followed by classroom stories and vibrant photos to illustrate the concepts. You will learn to create materials and a classroom culture reflecting your values; teach through observation, reflection, inquiry and action; and encourage children to represent their learning in multiple ways, including songs, stories, and drama'--
Includes bibliographical references and index.
Keywords: Early childhood education -- Curricula -- United States; Early childhood education -- Activity programs -- United States; Reflective teaching -- United States